PENGARUH METODE DEMONSTRASI DENGAN MENGGUNAKAN ALAT PERAGA TERHADAP HASIL BELAJAR FISIKA MATERI HUKUM II NEWTON PADA KELAS X DI SMA NEGERI 1 PANGKALAN LAMPAM KABUPATEN OGAN KOMERING ILIR - Bunga Harumsari; Muhammad Ali; Patricia Lubis (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The purpose of this study was to find out whether or not there was a significant effect of the demonstration method by using teaching aids on the physics learning outcomes of Newton's second law material in class X at Pangkalan Lampam 1 State High School. The variables of the study are veriabel bound, namely student learning outcomes and the variables of the practice, the demonstration method using props. The population in this study were all students of class X Science at SMA Negeri 1 Pangkalan Lampam which amounted to 115 students. The sample in this study was taken by purposive sampling technique with the number of samples of 80 students divided into two classes namely class X IPA 1 as the experimental class who received learning treatment using demonstration method with the number of 40 students and students of class X IPA 2 as the control class treated a conventional approach with a total of 40 students. Techniques of collecting data using tests and documentation. The analytical technique used in this study is the right-t test. The result of calculation of data analysis obtained the average value of experiments 81,00 and the average value of control class 73,75, with significant level α = 0,05 in ttable that is equal to 1,68 and titung that is 2,71. Based on the results of data calculations, it can be concluded that there is a significant influence of demonstration methods by using props to the results of physics study material law II Newton in class X in SMA Negeri 1 Pangkalan Lampam